Risk for pelvic metastasis and role of pelvic lymphadenectomy in node-positive vulvar cancer: results from the AGO-VOP.2 QS vulva study - Wölber, Linn; Hampl, Monika; Eulenburg, Christine Helene, Gräfin zu; Prieske, Katharina; Hambrecht, Johanna; Fürst, Sophie-Theresa; Klapdor, Rüdiger; Heublein, Sabine; Gass, Paul; Rohner, Annika; Canzler, Ulrich; Becker, Sven; et al. (Cancers, 2022)
The need for pelvic treatment in patients with node-positive vulvar cancer (VSCC) and the value of pelvic lymphadenectomy (LAE) as a staging procedure to plan adjuvant radiotherapy (RT) is controversial. In this retrospective, multicenter analysis, 306 patients with primary node-positive VSCC treated at 33 gynecologic oncology centers in Germany between 2017 and 2019 were analyzed. All patients received surgical staging of the groins; nodal status was as follows: 23.9% (73/306) pN1a, 23.5% (72/306) pN1b, 20.4% (62/306) pN2a/b, and 31.9% (97/306) pN2c/pN3. A total of 35.6% (109/306) received pelvic LAE; pelvic nodal involvement was observed in 18.5%. None of the patients with nodal status pN1a or pN1b and pelvic LAE showed pelvic nodal involvement. Taking only patients with nodal status ≥pN2a into account, the rate of pelvic involvement was 25%. In total, adjuvant RT was applied in 64.4% (197/306). Only half of the pelvic node-positive (N+) patients received adjuvant RT to the pelvis (50%, 10/20 patients); 41.9% (122/291 patients) experienced recurrent disease or died. In patients with histologically-confirmed pelvic metastases after LAE, distant recurrences were most frequently observed (7/20 recurrences). Conclusions: A relevant risk regarding pelvic nodal involvement was observed from nodal status pN2a and higher. Our data support the omission of pelvic treatment in patients with nodal status pN1a and pN1b.
Gesehen am 17.07.2023